Effect spraying of Broad Bean Vicia faba L with Nano composites and growth regulators on enhancing growth and productivity - علي, ثراء; رياض زيدان ,; جنان عثمان, (Latakia University Journal -Biological Sciences Series, 2024)
The research was conducted in Tishreen university during the period of 2021/2022 and 2022/2023, to determine the effect of some of Nanocomposites and growth regulators on enhancing growth and productivity of Broad Bean Vicia faba L. The study included nine treatments (T1 control without spraying, T2 Diamond , T3 Crystal, T4 Obar fix, T5 Casperfix, T6 Dimacomplex, T7 Gibberellin, T8 Kinetin, T9 Brassinolide ), The completely randomized design was used with three replications. The results showed that Tretment 5 spraying with Casperfix gave the superior results with significant difference in the most of vegetative indicator: ( height of plant, fresh and dry weight, leaf surface area and indicator). Crystal compound and growth regulators Gibberellin and Kinetin the highest value for yield of plant (1014.6 , 1076.4 , 1014.6) g/plant and production( 3.46 , 3.58, 3.40) kg/m2 respectively compared to the control 646 g/plant and 2.15 kg/m2. There isn’t any significant difference between the treatments in the content of dry meter, carbohydrate and protein. Whereas, Crystal gave the superior results with significant difference in S.S.T (8.96%), and Brassinolide the least value for content nitrate in pods (65.67mlg/kg).